Early‐pregnancy maternal vitamin D status and maternal hyperglycaemia. Issue 9 (13th June 2013) - Tomedi, L. E.; Simhan, H. N.; Bodnar, L. M.
Abstract Aims To estimate the association between serum 25‐hydroxyvitamin D concentrations and maternal hyperglycaemia (post‐load glucose concentration ≥ 7.5 mmol/l). Methods Pregnant women (n = 429; 61% black, 36% obese, 45% smokers) enrolled in a cohort study at <16 weeks gestation. Non‐fasting blood samples were assayed for serum 25‐hydroxyvitamin D at enrolment. At 24–28 weeks gestation, maternal hyperglycaemia was determined using a 50‐g 1‐h oral glucose challenge test. Results A total of 67% of women had 25‐hydroxyvitamin D concentrations < 50 nmol/l and 11% had maternal hyperglycaemia. Among smokers, each 23‐nmol/l increase in serum 25‐hydroxyvitamin D was associated with a reduction in the odds of maternal hyperglycaemia [odds ratio: 0.30 (95% CI: 0.13, 0.68)] after adjustment for parity, race/ethnicity, age, pre‐pregnancy BMI, marital status, income, family history of diabetes, and gestational age of gestational diabetes mellitus screening. Among non‐smokers, we found no association between early pregnancy vitamin D status and maternal hyperglycaemia. Conclusions Smoking status may modify the relationship between poor maternal vitamin D status and maternal hyperglycaemia.